A SURVEY OF BULLOUS DISEASES CLINICOEPIDEMIOLOGICAL CHARACTERISTICS - O.S. Imamov; J.A. Rizaev; G.Sh. Toxtayev (Central Asian Journal of Medicine, 2025)
Autoimmune bullous diseases, if left untreated, are life-threatening conditions affecting primarily skin and mucous membranes. These blistering disorders are characterized by epidermal or subepidermal detachment. Autoimmunity plays a key role in pathogenesis; therefore, immunosuppressive agents are the treatment of choice. The aim of this study is to document relative frequencies of different autoimmune bullous diseases, patient characteristics, treatment options, and side effects in patients presenting to our bullous skin diseases.